2022
DOI: 10.1093/nutrit/nuac088
|View full text |Cite
|
Sign up to set email alerts
|

Beyond lockdowns: a systematic review of the impacts of COVID-19 lockdowns on dietary pattern, physical activity, body weight, and food security

Abstract: Context COVID-19 lockdowns may have impacted dietary patterns and nutritional outcomes in many populations. Objective The aim of this review was to evaluate the impacts of COVID-19 lockdowns on nutritional patterns, investigating behaviors in the periods before, during, and after lockdowns. Data Source This systematic review followed the PRISMA-P methodology.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 49 publications
3
25
0
Order By: Relevance
“…Of these, 25 papers related to mental health impacts, 13 to healthcare delivery, 12 to infection control, 13 to economic impacts, 7 to social impacts, and 3 to impacts on education. In addition, we identified systematic reviews of impacts on mental health [ 87 , 88 , 89 , 90 , 91 ], physical activity [ 46 , 65 , 92 , 93 , 94 ], diet and nutrition [ 47 , 65 , 66 , 67 , 68 ], body weight and obesity [ 48 , 71 , 72 ], alcohol consumption [ 49 ], and tobacco smoking [ 50 , 95 ], which we present in summary below, along with individual primary research papers of particular interest.…”
Section: Review Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 25 papers related to mental health impacts, 13 to healthcare delivery, 12 to infection control, 13 to economic impacts, 7 to social impacts, and 3 to impacts on education. In addition, we identified systematic reviews of impacts on mental health [ 87 , 88 , 89 , 90 , 91 ], physical activity [ 46 , 65 , 92 , 93 , 94 ], diet and nutrition [ 47 , 65 , 66 , 67 , 68 ], body weight and obesity [ 48 , 71 , 72 ], alcohol consumption [ 49 ], and tobacco smoking [ 50 , 95 ], which we present in summary below, along with individual primary research papers of particular interest.…”
Section: Review Resultsmentioning
confidence: 99%
“…A subsequent systematic review by Mekanna et al (2022) [ 93 ] included studies of eating and lifestyle behaviours during and after lockdowns, which differed from those of the earlier reviews. These authors likewise found that PA generally decreased during lockdowns and, additionally, found that it increased again after the lockdowns were lifted, but they were unable to establish whether it returned to the pre-pandemic levels.…”
Section: Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The novel coronavirus disease 2019 (COVID-19) pandemic undeniably disrupted the lives of college students around the globe. The advent of this historic event and its prolonged progression has taken a significant toll on both the psychology and the behavioral health of youth and young adults, manifesting, frequently, as increases in poor dietary and other lifestyle choices [ 1 , 2 , 3 ]. These choices include unhealthy behaviors such as excess alcohol consumption [ 4 , 5 , 6 ], frequent binge eating [ 7 , 8 ], and the overconsumption of ultra-processed foods [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…8 Accordingly, many people reported more time spent sedentary, unfavorable changes to eating behaviors, and worsened anxiety and depression. 9,10 The pandemic had direct and indirect effects on pregnant individuals' everyday lives, including higher depression, 11 fewer prenatal and postpartum visits, 12,13 and increased early-pregnancy adverse outcomes. 14 These observations mirror disaster research, 15,16 which suggests that exposure to disasters during pregnancy leads to increased incidence of pregnancy loss, birth defects, and adverse child development.…”
Section: Introductionmentioning
confidence: 99%